Development of assisted reproductive technologies in small animal species for their efficient preservation and production - Keiji MOCHIDA (The Society for Reproduction and Development, 2020)
Assisted reproductive technologies (ARTs) are widely used in the animal industry, human clinics, and for basic research. In small laboratory animal species such as mice, ARTs are essential for the production of animals for experiments, the preservation of genetic resources, and for the generation of new strains of genetically modified animals. The RIKEN BioResource Research Center (BRC) is one of the largest repositories of such animal bioresources, and maintains approximately 9,500 strains of mice with a variety of genetic backgrounds. We have sought to devise ARTs specific to the reproductive and physiological characteristics of each strain. Such ARTs include superovulation, in vitro fertilization (IVF), the cryopreservation of embryos and spermatozoa, transportation of cryopreserved materials and embryo transfer (ET). Of these, superovulation likely has the most influence on animal production because it determines the quantity of starting material for other ARTs. Superovulation using anti-inhibin serum combined with estrous synchronization has resulted in approximately a three-fold increase in production efficiency with IVF-ET in the C57BL/6J strain. Wild-derived strains are important as genetically diverse resources for murine rodents (Genus Mus), and many are unique to the BRC. We have also successfully developed ARTs for more than 50 wild-derived strains, which have been cryopreserved for future use. Our work to improve and develop ARTs for mice and other small laboratory species will contribute to the cost-effectiveness of routine operations at repository centers, and to the provision of high quality animals for research use.